Effects of predator odour on antipredator responses of Nile tilapia - Miyai, Caio Akira [UNESP]; Sanches, Fábio Henrique Carretero [UNESP]; Pinho-Neto, Cândido Ferreira [UNESP]; Barreto, Rodrigo Egydio [UNESP] (Elsevier, 2016)
Several fish species exhibit antipredator responses when exposed to chemicals which indicate risk of predation. One such substance is the scent of a predator (a kairomone) that may induce defensive responses in a potential prey. In the present study, we show that chemical cues (odour) from predator fish induce antipredator and stress responses in Nile tilapia. When exposed to predator odour, Nile tilapia decreased activity and increased ventilation rate (VR), but no increase in plasma levels of cortisol and glucose was found. Although the hypothalamic-pituitary-interrenal axis (HPI axis) was not activated, an increase in ventilation is a fast response which can provide the fish enough oxygen for a ‘fight or flight’ event when facing a predator. Thus, this respiratory response suggests an anticipated adjustment in order to prepare the body for a defensive response, such as escaping, irrespective of HPI axis activation.
Keywords: Chemical cues; Cortisol; Glucose; Kairomone; Locomotion; Ventilation rate